Critical evaluation of paliperidone in the treatment of schizophrenia in Chinese patients: a systematic literature review - Zhang L; Li J; Zhao Y; Su Y; Si T (Neuropsychiatric Disease and Treatment)
LiLi Zhang,1 JiTao Li,2–4 YanJie Zhao,5 Yun’Ai Su,2–4 Tianmei Si2–4 1Medical Affairs, Xian Janssen Pharmaceutical Co, Ltd, 2National Clinical Research Center for Mental Disorders, 3Peking University Sixth Hospital, Institute of Mental Health, 4The Key Laboratory of Mental Health, Ministry of Health, Peking University, 5National Institute for Nutrition and Health, Chinese Center for Disease Control and Prevention, Beijing, People’s Republic of China Background: Paliperidone (9-hydroxyrisperidone), the major active metabolite of risperidone, has been introduced as a novel atypical antipsychotic agent in many countries. It is available both as an oral extended-release (ER) formulation and as a long-acting injection (paliperidone palmitate, PP), which have been approved for treating schizophrenia in the People’s Republic of China since 2009 and 2012, respectively. This systematic review summarizes the efficacy, effectiveness, and safety of paliperidone in the treatment of schizophrenia in the Chinese population. Methods: A systematic literature search was conducted on the databases covering international and Chinese core journals, published from January 1, 2008, to May 22, 2015. Results: A total of 122 publications were retrieved, of which 63 studies were identified for inclusion; most studies were related to paliperidone ER (n=53), nine were related to PP, and one study was related to both agents. Paliperidone ER demonstrated at least comparable efficacy with active comparators, including risperidone, olanzapine, ziprasidone, or aripiprazole, and was found to be superior with respect to the onset of action and improvement in the Personal and Social Performance Scale score. Paliperidone ER appeared to be associated with a lower risk of metabolic syndromes; the most common treatment-emergent adverse events were extrapyramidal symptoms, akathisia, insomnia, and somnolence. Results from interventional and observational studies showed that PP was also an effective and well-tolerated treatment for Chinese patients with schizophrenia. The findings were generally consistent with those observed in non-Chinese populations. Conclusion: Both paliperidone ER and PP were effective and well-tolerated agents for the treatment of schizophrenia in the Chinese population according to the data we reviewed. No new safety signals specific for the Chinese population were raised for paliperidone. Further studies may be needed to collect more data on long-term treatment of schizophrenia in the People’s Republic of China. Keywords: paliperidone, antipsychotics, efficacy, effectiveness, safety